Neurologic and Neuroscientific Evidence in Aged COVID-19 Patients - Mainali, Shraddha; Darsie, Marin E. (Frontiers in Aging Neuroscience, 2021)
The COVID-19 pandemic continues to prevail as a catastrophic wave infecting over 111 million people globally, claiming 2.4 million lives to date. Aged individuals are particularly vulnerable to this disease due to their fraility, immune dysfunction and higher rates of medical comorbidities, among other causes. Apart from the primary respiratory illness, this virus is known to cause multi-organ dysfunction including renal, cardiac, and neurologic injuries, particularly in the critically ill cohorts. Elderly patients 65 years of age or older are known to have more severe systemic disease and higher rates of neurologic complications. Morbidity and mortality is very high in the elderly population with 6-930 times higher likelihood of death compared to younger cohorts, with the highest risk in elderly patients ≥85 years and especially those with medical comorbidities such as hypertension, diabetes, heart disease and underlying respiratory illness. Commonly reported neurologic dysfunctions of COVID-19 include headache, fatigue, dizziness and confusion. Elderly patients may manifest atypical presentations like fall or postural instability. Other important neurologic dysfunctions in the elderly include cerebrovascular diseases, cognitive impairment and neuropsychiatric illnesses. Elderly patients with preexisting neurological diseases are susceptibility to severe COVID-19 infection and higher rates of mortality. Treatment of neurologic dysfunction of COVID-19 is based on existing practice standards of specific neurological condition in conjunction with systemic treatment of the viral illness. The physical, emotional, psychologic and financial implications of COVID-19 pandemic have been severe. Long-term data are still needed to understand the lasting effects of this devastating pandemic.